PENDIDIKAN KARAKTER PADA ANAK DALAM PENDEKATAN ISLAM DAN PSIKOLOGI - Zainal Azman (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2018)
Child’s Character Building in Islamic and Psychological Approaches. Character or good morals of a child will not be materialized as such without going through the process of education. One way to improve the good character in children is to adapt to religious education from an early age. The author concludes that Islam and psychology perceive similar views and goals in comprehending child’s character building. In carrying outthe process of religious educationfor children in the family, the parentis requiredto use appropri atetechniques and approaches that it may affect personal development ofthe childin accordancewith Islamic educational objective, namely developing the character and psychological aspects. One of the methods that should be applied is the religion. In Islamic religious education and theory of psychology important principles are thought, such as: creed, exemplar, discipline, guidance, law, discipline, reward and punishment, all which will produce true believers, observance and good character. Thethree aspets will consequently lead tothe formation ofgood character, especiallymoral education.